2012
DOI: 10.1159/000336045
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Submacular Suprachoroidal Drug Administration via a Microcatheter: Retrospective Analysis of European Treatment Results

Abstract: Purpose: To investigate the safety and feasibility of using a microcatheter for drug delivery in the suprachoroidal space in eyes with advanced, exudative, age-related macular degeneration (AMD) unresponsive to conventional therapy. Procedures: A unique microcatheter was used to deliver a drug combination consisting of bevacizumab and triamcinolone to the submacular suprachoroidal space. Twenty-one eyes of 21 patients with choroidal neovascularization (CNV) secondary to advanced, exudative AMD were followed ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…Of particular interest, and the subject of human clinical trials [34, 35], is targeting the choroid and adjacent retina, for example, with steroids to treat inflammation, as well as other drugs. We have also recently proposed targeting drug delivery to the ciliary body via the anterior SCS for treatment of glaucoma [36].…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest, and the subject of human clinical trials [34, 35], is targeting the choroid and adjacent retina, for example, with steroids to treat inflammation, as well as other drugs. We have also recently proposed targeting drug delivery to the ciliary body via the anterior SCS for treatment of glaucoma [36].…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously reported using the suprachoroidal space for drug targeting to the choroid and adjacent retina to reach posterior segment targets (Morales-Canton V, et al IOVS 2013;54:ARVO EAbstract 3299). [17][18][19][20][21][22][23] Here, we accessed the ciliary body in the anterior segment by injecting drug into the most anterior portion of the suprachoroidal space, which we are calling the supraciliary space. By localizing the drug in the supraciliary space, we expected to achieve high drug levels locally in the adjacent ciliary body.…”
mentioning
confidence: 99%
“…[17][18][19][20][21][22][23] Researchers have Copyright 2014 The Association for Research in Vision and Ophthalmology, Inc. www.iovs.org j ISSN: 1552-5783 accessed the suprachoroidal space using surgically introduced catheters and conventional hypodermic needles, but more recently, our group introduced the use of microneedles as a simple and reliable method for suprachoroidal injection that is expected to be suitable for use as a rapid office procedure. 19 A first-in-humans study recently demonstrated injection of bevacizumab into the suprachoroidal space of four human eyes by using a microneedle (Morales-Canton V, et al IOVS 2013;54:ARVO E-Abstract 3299).…”
mentioning
confidence: 99%
“…The retinal pigment epithelium and pigmented choroid serve as a readily identifiable plane to dissect to. Once the sclerotomy is completed, a blunt-tipped catheter can be used to tunnel through the SCS towards the posterior pole[28, 32, 33, 37, 40, 41]. A catheter with a flashing diode has been used to visualize the advancement of the catheter under a microsurgical scope[28, 33].…”
Section: Accessing the Suprachoroidal Spacementioning
confidence: 99%